Perception of Self-Directed Learning Among Undergraduate and Postgraduate Students at Shaikh Zayed Hospital, Lahore - Aflak Rasheed, (Indus Journal of Bioscience Research, 2024)
Objectives: The main objective of this study was to examine changes in the perception and practice of self-directed learning by students in medical schools as influenced by different demographic factors. In general, the study aimed to assess disparities in SDL perceptions in gender, education level, and age, which would have implications for targeted educational designs and support structures that encourage SDL among students at various stages of their studies in medicine. Material and Methods: A total of 150 students from the Shaikh Zayed Hospital participated in this study. The sample consisted of males and females, with all stages of medical education representing 3rd year=2%, 4th year=32%, last year=62%, and last year postgraduate=4%. The age distribution was mostly–21-26years, with concentrations at age 22 (36 %) and age 23 (32 %). Data were collected using a structured questionnaire specifically designed to assess students' perceptions of self-directed learning and were analysed for trends and patterns. Results: The results pointed out a gender distribution showing an edge towards males with a significant representation of final-year students. The age data mentioned that most students belonged to the early twenties. The demographics indicate that SDL perceptions would vary with the stage of medical education and age. Final-year students might require SDL differently than their counterparts in the earlier years. Conclusion: This suggests that the perceptions of SDL, on the part of the students, differ by educational level and age. The closer an end-year student is to entering the profession, a person's SDL needs can differ from those of junior colleagues. The outcomes provide support for targeted SDL in response to differences in individual developmental stages and levels of educational readiness.